Prenatal dexamethasone exposure and developmental programming of the ovary of the offspring: a structural study in the rat - Risti, Nataša; Nestorovi, Nataša; Manojlovi-Stojanoski, Milica; Trifunovi, Svetlana; Ajdžanovi, Vladimir; Filipovi, Branko; Pendovski, Lazo; Miloševi, Verica (My University, 2021)
Overexposure to glucocorticoids during fetal development alters fetal organ growth and maturation patterns, which can result in adverse programming outcomes in adulthood. The aim of this study was to determine whether exposure to dexamethasone (Dx) during the fetal period programmed ovary development and function in infant (16-day-old) and peripubertal (38-day-old) female offspring. Pregnant Wistar rats were separated into control and Dx-treated (0.5mg kg-1) groups and were injected with Dx or an equivalent volume of vehicle on Days 16, 17 and 18 of gestation. Ovaries from 16- and 38-day-old female offspring were prepared for histological and stereological examination. The volume of the ovary and the number of primordial and primary follicles were significantly reduced in prenatally Dx-exposed infant and peripubertal female offspring compared with control offspring. The number of multilaminar follicles was decreased in infant female offspring. In peripubertal females, prenatal exposure to Dx increased the number of multilaminar and large follicles of all classes. Because vaginal opening did not occur up to Day 38 postpartum in the Dx-exposed offspring, the absence of ovulation and corpora lutea is confirmation that the onset of puberty had been delayed. We can conclude that overexposure to glucocorticoids early in life programs ovary development, which may affect fertility in adulthood.